Offshoring Accounting Services: New Opportunities for Developing Countries - Jadranka Mrsik; Ninko Kostovski (Journal of Accounting and Management Information Systems (JAMIS), 2017)
The aim of this paper is to explore the viability of off-shoring of accounting services to foreign companies by providers of such services located in Republic of Macedonia. We have assessed the potentials of accountants in Republic of Macedonian to offer off-shored accounting services by using the criteria for assessment of outsourcing destinations in general as established by the McKinsey Institute. We have founded that there is considerable potentials for off-shoring of accounting and related services. Exploitation of these potentials would result in significant contribution to the accounting profession development and the employment of young graduates in accounting. In these terms, we offer some practical recommendations to the profession and to the policy-makers for further promotion of this business opportunity.
Keywords: M14; M16; M41; 650; Accounting Services; Outsourcing; Off-shoring; Accountants